Composite t(14;18)-Negative Follicular Lymphoma and Nodular Lymphocyte-Predominant Hodgkin Lymphoma. (2nd August 2018) - O'Neill, John Patrick; Quinn, Fiona; Dowling, Anita; Walker, Jan; Hayes, Triona; Bird, Brian; Flavin, Richard
Abstract : A composite lymphoma is the rare simultaneous occurrence of two or more distinct lymphomas within a single tissue or organ. Herein, we describe a case of a 51-year-old man presenting with a history of lower limb rash, fatigue, and bulky abdominopelvic lymphadenopathy. An excisional left iliac lymph node biopsy was notable for the composite presence of two distinct lymphoid neoplasms, nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL), and follicular lymphoma (FL). Multiplex PCR and FISH analyses failed to demonstrate a t(14;18)(q32;q21) translocation in either composite lymphoma component. A clonal light-chain kappa (V/JC intron-kde) gene rearrangement was detected in the FL component only.